Disaggregation of the Role of Government Spending on the Economy and Community Welfare of Balikpapan City - Abdulloh; Nasikh; Siti Markhamah (Riviera Publishing, 2023)
Introduction: Balikpapan City is an example of an area in East Kalimantan Province that is in the final stage of development, which requires that government spending is no longer directed at providing physical infrastructure and facilities but is already directed at developing human resources and community welfare. This study is intended to examine the strength of the relationship between local government spending and other economic variables which are part of the main objective of implementing fiscal policy in the form of regional spending, including economic activity in the sectors of Manufacturing Industry, Construction, Transportation and Warehousing, Wholesale and Retail Trade; Repair of Cars and Motorcycles, and Financial Services, as well as social welfare in terms of the Open Unemployment Rate and the Percentage of Poor Population. Method: This study uses the Kendall Correlation Coefficient to test relationships between variables. Result: Based on the results of the study shows that regional spending has a significant impact on reducing the open unemployment rate in the City of Balikpapan. However, there is no significant relationship between regional spending and a reduction in the poverty rate. In addition, only operating expenditures play an essential role in economic development in Balikpapan City. In contrast, capital expenditures do not have a significant influence. Conclusion: Local governments can strengthen operating spending to boost economic growth and reduce unemployment rates. The government also needs to consider the time lags in planning and using capital expenditures so that they have a more effective impact on advancing the economy.